EFEKTIFITAS LATIHAN TAI CHI TERHADAP PENINGKATAN KESEIMBANGAN STATIS DAN DINAMIS (STUDI KUASI EKSPERIMEN : PADA LANSIA DI PSTW BUDI MULYA I TAHUN 2022) - Rovika Trioclarise; Ratu Karel Lina; Nina Mustikasari (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Elderly is a life cycle marked by a decrease in physiological body functions, one of which is related to a decrease in balance, namely a decrease in muscle strength, changes in posture, a decrease in proprioception, and a decrease in visual. Tai Chi is an exercise that involves a lot of multi-sensory factors that can improve the balance of the elderly. The purpose of this study was to determine the effect of Tai Chi on the balance of the elderly. Research Design: Quasi experimental using “Two-group pretest-posttest design. The research population is all the elderly in PSTW Cipayung. The results of the sample count were 15 people per group, a total of 30 people. The independent variable in this study was the Elastic Band Exercise intervention. The dependent variable is the balance of the elderly. This research will be conducted in April – September 2022. Data collection uses a balance assessment instrument and then the Elastic Band Exercise intervention. Data analysis was carried out univariate and bivariate. The results of statistical tests prove that there is a significant difference in the average static and dynamic balance in the elderly in the intervention group (p = 0.0001), there is no significant difference in the average static and dynamic balance in the elderly in the control group (p = 0.499), and there was a significant difference in the mean of Static and Dynamic Equilibrium between the intervention group and the control group (p= 0.0001). Suggestions are given so that the elderly can practice Tai Chi Gymnastics regularly, always maintain a calm mood of the elderly, relax so that they are not stressed and short-term memory is not disturbed.